AKTIVITAS ANTIOKSIDAN KOMPLEKS KITOSAN MONOSAKARIDA (Chitosan Monossacharides Complex) - Selly Ratna Sari; Ace Baehaki; Shanti Dwita Lestari (Jurnal FishtecH, 2013)
The purpose of this research was to observe antioxidative activity of chitosan monosaccharides complex. The research was conducted in May until June 2013 at chemistry and microbiology laboratory, study program of agricultural technology. All treatment are chitosan, chitosan glucose complex, chitosan galactose complex and chitosan fructose complex using a invitro testing. The parameters were brown color analysis, analysis antioxidant activity with DPPH and reducing power method . The result showed that all chitosan monosaccharides complex demonstrated better antioxidative than chitosan. It is indicated that Maillard reaction product (MRP) exhibited antioxidant activity. The brown color analysis (0.031-0.224), antioxidant antioxidant analysis with DPPH method of IC50 (92-131 ppm) and reducing power method was 1.059-1.274. Chitosan galactose complex (A2) is the best to antioxidative from all treatments. Chitosan monosaccharides complex could be used as natural preservatives, edible packaging (film and couting) and food additive.